Manfred Wörner's Last Interview (Czech Journal of International Relations, 1994)
Our Parisian colleague Jacques Rupnik, a member of the editorial circle of this magazine, gave us his interview with Manfred Worner shortly before his sudden death (August 13, 1994). It is the last interview of the unforgettable NATO Secretary General, who served in this capacity for a full six years (since July 1988) and served to successfully begin the transformation of the North Atlantic Alliance into a security structure of a pan-European nature. The agreed title of the interview is indicative of Worner's thinking and measurement: The New Face of NATO.Jacques Rupnik: After the end of the Cold War, the old continent seems to be undergoing a major transformation. Following the revolutionary changes in Russia, the Balkans or Central Europe, how should the role of NATO change?